Chromatin dynamics in pollen mother cells underpin a common scenario at the somatic-to-reproductive fate transition of both the male and female lineages in Arabidopsis - She, Wenjing; Baroux, Célia (Frontiers in Plant Science, 2015)
Unlike animals, where the germline is established early during embryogenesis, plants set aside their reproductive lineage late in development in dedicated floral organs. The specification of pollen mother cells (PMCs) committed to meiosis takes place in the sporogenous tissue in anther locules and marks the somatic-to-reproductive cell fate transition towards the male reproductive lineage. Here we show that Arabidopsis PMCs differentiation is accompanied by large-scale changes in chromatin organization. This is characterized by significant increase in nuclear volume, chromatin decondensation, reduction in heterochromatin, eviction of linker histones and the H2AZ histone variant. These structural alterations are accompanied by dramatic, quantitative changes in histone modifications levels compared to that of surrounding somatic cells that do not share a sporogenic fate. All these changes are highly reminiscent of those we have formerly described in female megaspore mother cells (MMCs). This indicates that chromatin reprogramming is a common underlying scenario in the somatic-to-reproductive cell fate transition in both male and female lineages.